2022
DOI: 10.1038/s41598-022-24843-w
|View full text |Cite
|
Sign up to set email alerts
|

A conserved MTMR lipid phosphatase increasingly suppresses autophagy in brain neurons during aging

Abstract: Ageing is driven by the progressive, lifelong accumulation of cellular damage. Autophagy (cellular self-eating) functions as a major cell clearance mechanism to degrade such damages, and its capacity declines with age. Despite its physiological and medical significance, it remains largely unknown why autophagy becomes incapable of effectively eliminating harmful cellular materials in many cells at advanced ages. Here we show that age-associated defects in autophagic degradation occur at both the early and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…These results indicate that autophagic activity gradually lowers with age in the examined tissue. Similar data have been previously obtained from other Drosophila tissues, including the nervous system [30,43]. Next, Ref(2)P levels were compared in the IFM between control and AUTEN-67/99-treated animals.…”
Section: Auten-67 and -99 Induce Autophagy In The Drosophila Striated...supporting
confidence: 54%
See 2 more Smart Citations
“…These results indicate that autophagic activity gradually lowers with age in the examined tissue. Similar data have been previously obtained from other Drosophila tissues, including the nervous system [30,43]. Next, Ref(2)P levels were compared in the IFM between control and AUTEN-67/99-treated animals.…”
Section: Auten-67 and -99 Induce Autophagy In The Drosophila Striated...supporting
confidence: 54%
“…For example, muscle regeneration characterizing mammalian organisms, as well as the age-related loss of muscle mass, cannot be examined in the fruit fly [59][60][61][62]. As in the nervous system, the IFM has been shown to increase EDTP expression with age [30,31,63]. If the age-dependent increase in EDTP expression causes harmful protein dephosphorylation in muscle, it may be important to investigate the effect of AUTENs on phosphatase activity in IFM ageing in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following Drosophila stocks were used for gene silencing: 40D-UAS (as an RNAi control—VDRC:60101), w 1118 ; P{GD11800}v40337 (UAS-Rab7-RNAi—VDRC: 40337), w * , Arl8[NIG.7891R (UAS-Arl8-RNAi—VDRC: 7891R-2), P{KK107630}VIE-260B (UAS-Rab2-RNAi—VDRC: v105358). We also used y 1 w * ; P{w[+mC] = UAST-YFP.Rab2}l(3)neo38 02 /TM3, Sb 1 (UAS-Rab2-WT—BDSC:23246) flies to compare the overexpression of wild-type Rab2 to the overexpression of a constitutively active form of Rab2 (Rab2 CA), and y * w * ; P{UAS-Luc.VALIUM20}attP40 (UAS-Luc—gift of Tamás Lukácsovich [ 52 ]) to compensate 2 Gal4 sequences in a PD model w * ; P{UAS-Hsap\SNCA.A53T} [ 15 ]. (UAS-A53T—BDSC:8148).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that autophagic capacity gradually decreased in the brains of flies during ageing. In aged animals, decreased levels of early markers of autophagy, e.g., FYVE (Fab-1, YGL023, Vps27, and EEA1 domain)- and Atg5-labeled structures, indicate that fewer autophagosomes are formed, but the increased amount of Atg8a-positive structures and accumulation of lipid-conjugated Atg8a (Atg8a-II) show that autophagy is also impaired after autophagosome formation (when the structure fuses with a lysosome or the autolysosomal content is digested enzymatically) [ 52 ]. Thus, autophagy gradually declines with age in brain neurons due to the cumulative effect of suppressed autophagosome formation and compromised autolysosomal function.…”
Section: Introductionmentioning
confidence: 99%